Investigation of Ground Vibration Induced by Blasting at Hisarcik Boron Open Pit Mine in Turkey - Ali Kahriman; Gungor Tuncer (International Society of Explosives Engineers, 2006)
This paper presents the results of ground vibration measurements carried out in Hisarcik Boron open pit mine located on the west side of the central Anatolia near Kütahya province in Turkey. Within the scope of this study in order to predict peak particle velocity level for this site, ground vibration components were measured for 304 shots during bench blasting. In blasting operations; ANFO (blasting agent), gelatin dynamite (priming) and delay electric detonators (firing) were used as explosives. Parameters of scaled distance (charge quantity per delay and the distance between the source and the station) were recorded carefully and the ground vibration components were measured for all blast events using 2 different types vibration monitors (1 White Mini-Seis and 1 Instantel Minimate Plus Models). The absolute distances between shot points and monitor stations were determined using GPS. The equation of square root scaled distance extensively used in the literature was taken into consideration for the prediction of peak particle velocity.